PROFILE ATHLETES IN HIGH IMPACT URINARY INCONTINENCE IN FEMALES (Fiep Bulletin - online, 2011)
Urinary incontinence is defined as any involuntary loss of urine, and can bring many negative consequences for quality of life of women. The high impact sports or abrupt movements can trigger urinary incontinence in athletes, the impact force to the pelvic floor and increased into-abdomen pressure. In this context, therefore this study aims to evaluate the profile of athletes with high-impact urinary incontinence in women. This is a study of a prospective, descriptive and quantitative approach, through field research, conducted in April and May 2010, taking place as a private school in São Luís – MA, were interviewed 11 volleyball players, 13 basketball and 12 handball players. The results showed that there is a relationship of dependency between the situation determinant of urinary incontinence and the different moments of physical activities in three modalities investigated. Regarding the time of exercise modality, the highest percentage of athletes in basketball, with more than five years of playing sports. Identifying the profile of athletes provides physical therapy specializing in women's health and reduce risks from the intense efforts of high-impact activities.
Keywords: Urinary incontinence; Pelvic floor; High-impact athletes